Impact of Orange flesh sweet potato flour incorporation on micronutrient, dough characteristics and consumer’s acceptability of bread - Adedokun, Isiaka Ishola; Ekeocha, Peace; Awoyale, Wasiu; Agbaje, Rafiu; Abass, Sekinat (Indonesian Food and Nutrition Progress, 2025)
Evaluation of micronutrient contents of composite flour, dough characteristics, and sensory properties of bread from wheat and orange-flesh-sweet potato flour blend was carried out. Orange flesh sweet potato flour was used to replace wheat flour  in ratios of 90:10%, 80:20%, 70:30%, and 60:40% of wheat and orange flesh sweet potato flour, respectively. The formulated composite flour was used for the baking of bread, a control bread sample was produced from 100% wheat flour. Composite flour and 100% wheat flour were subjected to provitamin A and mineral analyses, and physical characteristics of the dough and sensory properties of the bread samples were also evaluated using standard methods. The values obtained on all analyses evaluated in this work were significantly different among the samples (p<0.05).  Provitamin A and mineral content of the flour increased as the level of orange flesh sweet potato flour increased (10% to 40%). Provitamin A content of the flour increased from 5.62 mg/100 g to 50.31 mg/100 g, calcium 10.99 mg/100 g to 14.88 mg/100 g, potassium 310.47 mg/100 g to 367.43 mg/100 g, and phosphorous increased from 7.24 mg/100 g to 11.57 mg/100 g. On the other hand, magnesium, iron, and zinc decreased gradually from 50.10 to 31.08 mg/100 g of magnesium, 3.38 mg/10 g to 2.01 mg/100 g and 8.01 to 6.87 mg/100 g in the flour samples. Physical characteristics of the dough were not the same; loaf volume decreased from 271.08 to 160.43 cm3 while loaf specific volume decreased from 1.39 to 0.71, but loaf weight increased from 180.62 to 234.10 g as the level of orange flesh sweet potato flour increased from 10 to 40%. In addition, the mean preference for sensory properties such as crust colour, taste, and overall acceptability of bread loaves samples was not the same (p>0.05). Generally, the composite bread incorporated with 10% orange flesh sweet potato having 6.90 mean score was closely related to the control sample in terms of overall acceptability. Indications from quality characteristics and organoleptic properties assessed shown the potential of orange flesh sweet potato flour for improving the nutritional and consumers’ acceptability of bread.